The Impact of Trust, Satisfaction, and Perceived Quality on Preference for Setting of Future Care Among Veterans With PTSD. Issue 11 (20th April 2019) - Haro, Elizabeth; Mader, Michael; Noël, Polly H; Garcia, Hector; Vogt, Dawne; Bernardy, Nancy; Bollinger, Mary; Pugh, Mary Jo V; Finley, Erin P
Abstract: Introduction: Among US veterans, posttraumatic stress disorder (PTSD) is a high-prevalence condition; more than a million veterans of all combat eras are service-connected for this condition. Research on factors driving veterans' decision-making regarding preferred setting for PTSD care has been limited. The purpose of this study was to understand factors associated with preferences for setting of future PTSD care among veterans service-connected for PTSD. Materials and Methods: We conducted a cross-sectional mailed survey among veterans with service connection for PTSD in Texas and Vermont identified from the Veterans Services Network Corporate Mini Master File (VETSNET). Survey items were intended to elucidate PTSD healthcare decision-making and queried utilization, perceived need for care, and satisfaction and preferences for VA, community, and/or military setting for receipt of future PTSD care. Logistic regression was used to identify factors associated with preference for care setting. UT Health San Antonio's Institutional Review Board determined this quality improvement project to be non-research. Results: Veterans ( n = 2, 327) were surveyed with an overall response rate of 37.1%. Most veterans (72.4%) identified VA as a preferred site for their future PTSD care; a substantial, but smaller, number of veterans identified being interested in receiving care in community (39.9%) and military (12.7%) settings. Factors associated with preferences for future care setting included demographics (e.g., ethnicity, income), availability of healthcare coverage, prior experiences of care, and attitudes related to perceived quality of care and trust in VA. Conclusions: These findings suggest that it is important to retain foundational mental health services within VA, as well as to continue to invest in building provider and network capacity in community settings, to ensure alignment with veteran preferences for care setting.